The Impact of Unstable Taxa in Coelurosaurian Phylogeny and Resampling Support Measures for Parsimony Analyses - Pol, Diego (2020)
Paleontological datasets often have large amounts of missing entries that result in multiple mostparsimonious trees. Highly incomplete and conflictive taxa produce a collapsed strict consensus andseveral methods have been developed for identifying these unstable or rogue taxa in optimal treesderived from phylogenetic analyses. In addition to decreasing consensus resolution, incomplete orconflictive taxa can also severely affect the support values of phylogenetic analysis in paleontologicaldatasets. Here, we explore a protocol for the identification of taxa that decrease jackknife supportvalues in parsimony analysis. The taxa identified are excluded from majority rule jackknife trees,revealing nodes that have either low or high support irrespective of the uncertainties in the placement of unstable taxa. A recently published dataset of coelurosaurian relationships based on 164taxa and 853 characters is explored using this protocol; our protocol detects a total of 40 unstabletaxa as the most detrimental for node supports. Major clades that are well supported in the reducedjackknife tree include Coelurosauria, Maniraptoriformes, Compsognathidae, Ornithomimosauria,Alvarezsauroidea, Therizinosauria, Oviraptorosauria. Clades with moderate support instead includeManiraptora, Pennaraptora, Paraves, Dromaeosauridae, Troodontidae, Anchiornithinae, and earlydiverging clades of Avialae.